ILCA Bulletin No. 14 - Animal traction in sub-Saharan Africa - International Livestock Centre for Africa (International Livestock Centre for Africa, 1981)
Discusses the use of animal traction for agriculture in sub-Saharan Africa, evaluating its actual and prospective contribution, bio-climatic, traditional and historical factors influencing ways in which animal traction is used and constraints arising from the characteristics of local breeds, equipment, feed resources, farmers' attitudes, as well as management and financing. Assesses effects of development efforts on productivity, farm income and overall economic development.